Reactivity of Fibrinogen Crosslinking Sites in the Absence of Thrombin - Seelich, Thomas; Furlan, Miha; Beck, Eugen A. (Thrombosis and Haemostasis, 1976)
The reactivity of fibrinogen crosslinking sites with thrombin-free, preactivated factor XIII (F. Xllla) was investigated under different conditions such as increased ionic strength, presence of urea, protamine sulfate (PS) or of varying concentrations of monodansylcadaverine (MDC). Crosslinking and incorporation of MDC into fibrinogen or fibrin γ- and α-chains were evaluated by SDS-Polyacrylamide gel electrophoresis.According to our results, rates of crosslinking of, and of MDC incorporation into, both γ-and α-chains of fibrinogen were low under physiological conditions; they were not significantly influenced by the presence of either 1.0 M NaCl or 1.0 M urea. In contrast, 0.01 % PS precipitated fibrinogen, and, simultaneously, significantly increased the rates of crosslinking and of MDC incorporation into both γ- and α-chains. MDC, at concentrations above approximately 6 mM, also precipitated fibrinogen, and, up to a concentration of about 9 mM, markedly enhanced the reactivity of acceptor crosslinking sites.Our results suggest that solubility of fibrinogen and the conformational arrangement of its subunit chains are closely interdependent; the reactivity of crosslinking sites with F. Xllla seems to be a function of this conformational state.